Analisis Kualitas Pelayanan Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Di Mall Pelayanan Publik Kabupaten Sleman - Wasis Wasis (CV. ULIL ALBAB CORP, 2025)
The purpose of this research is to analyze the quality of BPJS Ketenagakerjaan services at the Public Service Mall in Sleman Regency. The research method used is descriptive qualitative, the authors describe the situation regarding the implementation of BPJS Ketenagakerjaan services at the Sleman Public Service Mall as a form of excellent service implementation in administrative reform. From the results of the analysis, it is known that the quality of service at the BPJS Ketenagakerjaan Public Service Mall in Sleman Regency is still not optimal with several problems related to employee commitment and relatively narrow service spaces.